(x-7)(x+2)=17

Simple and best practice solution for (x-7)(x+2)=17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-7)(x+2)=17 equation:


Simplifying
(x + -7)(x + 2) = 17

Reorder the terms:
(-7 + x)(x + 2) = 17

Reorder the terms:
(-7 + x)(2 + x) = 17

Multiply (-7 + x) * (2 + x)
(-7(2 + x) + x(2 + x)) = 17
((2 * -7 + x * -7) + x(2 + x)) = 17
((-14 + -7x) + x(2 + x)) = 17
(-14 + -7x + (2 * x + x * x)) = 17
(-14 + -7x + (2x + x2)) = 17

Combine like terms: -7x + 2x = -5x
(-14 + -5x + x2) = 17

Solving
-14 + -5x + x2 = 17

Solving for variable 'x'.

Reorder the terms:
-14 + -17 + -5x + x2 = 17 + -17

Combine like terms: -14 + -17 = -31
-31 + -5x + x2 = 17 + -17

Combine like terms: 17 + -17 = 0
-31 + -5x + x2 = 0

Begin completing the square.

Move the constant term to the right:

Add '31' to each side of the equation.
-31 + -5x + 31 + x2 = 0 + 31

Reorder the terms:
-31 + 31 + -5x + x2 = 0 + 31

Combine like terms: -31 + 31 = 0
0 + -5x + x2 = 0 + 31
-5x + x2 = 0 + 31

Combine like terms: 0 + 31 = 31
-5x + x2 = 31

The x term is -5x.  Take half its coefficient (-2.5).
Square it (6.25) and add it to both sides.

Add '6.25' to each side of the equation.
-5x + 6.25 + x2 = 31 + 6.25

Reorder the terms:
6.25 + -5x + x2 = 31 + 6.25

Combine like terms: 31 + 6.25 = 37.25
6.25 + -5x + x2 = 37.25

Factor a perfect square on the left side:
(x + -2.5)(x + -2.5) = 37.25

Calculate the square root of the right side: 6.103277808

Break this problem into two subproblems by setting 
(x + -2.5) equal to 6.103277808 and -6.103277808.

Subproblem 1

x + -2.5 = 6.103277808 Simplifying x + -2.5 = 6.103277808 Reorder the terms: -2.5 + x = 6.103277808 Solving -2.5 + x = 6.103277808 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + x = 6.103277808 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + x = 6.103277808 + 2.5 x = 6.103277808 + 2.5 Combine like terms: 6.103277808 + 2.5 = 8.603277808 x = 8.603277808 Simplifying x = 8.603277808

Subproblem 2

x + -2.5 = -6.103277808 Simplifying x + -2.5 = -6.103277808 Reorder the terms: -2.5 + x = -6.103277808 Solving -2.5 + x = -6.103277808 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + x = -6.103277808 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + x = -6.103277808 + 2.5 x = -6.103277808 + 2.5 Combine like terms: -6.103277808 + 2.5 = -3.603277808 x = -3.603277808 Simplifying x = -3.603277808

Solution

The solution to the problem is based on the solutions from the subproblems. x = {8.603277808, -3.603277808}

See similar equations:

| 19x+16=86 | | p-13=31 | | a(x)+b=c | | 7e-4(6+2w)=3(w-8) | | -4(5x-7)+1=20x+29 | | 25x+20=78 | | 47x=46x+1 | | 60+4n=76 | | 40x+18=86 | | 3(x+2)-8x=4x+1 | | 20x-10=110 | | 30x-18=150 | | 12=v+2 | | (4+4i)+(-5+7i)-8i= | | 8(-3b+6)=96 | | 1.3n-.03=9 | | 4xy^2/y | | 20×1/4 | | x^2-40=41 | | 3(2l+10)=48 | | y+x=10-4 | | 3x+22=x+4 | | 0.6(x-1)+0.2x=6.6 | | y=-2.1x+3.4 | | -x-19=2x+8 | | 49=-7z | | y=2x^2-36x+c | | -2(x+2)+3=3(x+3)+4 | | (x-2)(x-2)+(y-6)(y-6)=25 | | 2+f=-3 | | x-6+x=78 | | -y/4=-16 |

Equations solver categories